FASILITAS DAN SISTEM KOMPENSASI DAMPAKNYA PADA KINERJA KARYAWAN DI BANK BJB SYARIAH KCP. KUNINGAN - Apriyani, Regi Destanti; Rahmat, Biki Zulfikri; Nasrulloh, Agus Ahmad (JURNAL EKONOMI SYARIAH, 2021)
Good employee performance will be achieved if you pay attention to what factors can influence it. The case that occurred at Bank BJB Syariah KCP Kuningan was that employees complained about work facilities and the compensation system. The method used in this study is a descriptive method with a qualitative approach. With two data sources, namely primary data sources consisting of leaders and all employees at Bank BJB Syariah KCP. Brass and secondary data sources consisting of documents both in writing and photos at Bank BJB Syariah KCP. Brass. Data collection techniques used are interviews, observation and documentation. The research instrument is the researcher himself as the main instrument in the research, observation guide and interview guide. The results showed that the facilities provided by Bank BJB KCP. Kuningan is inadequate, the internet network is often disturbed, the lack of operational vehicles, the parking area is not large enough, thus disrupting employee performance. As for compensation, the institution has given it fairly and fairly well in accordance with existing regulations. Both of these things certainly have an impact on employee performance, so that it can be said that the failure of the BJB Syariah Bank, Kuningan Sub-Branch Office, has not been able to meet the needs to improve employee performance.